The Effect of Repeated Sprint Ability Training on the Speed Endurance of Backs in Bandung City Rugby Sevens - Hutauruk, Difannes De Monang; Febrianty, Mona Fiametta; Novian, Geraldi (Indonesian Journal of Physical Education and Sport Science, 2026)
Study Purpose. This study aims to determine the effect of Repeated Sprint Ability (RSA) training on the speed endurance of backs in the Bandung City rugby sevens team. Material and Methods. The method used was a quasi-experimental study with a randomized pretest–posttest control group design. The sample consisted of 20 athletes divided into an experimental group (10 athletes) and a control group (10 athletes). The experimental group underwent an RSA training program for four weeks, with three sessions per week, while the control group followed the team's regular training schedule. The measurement instrument used was the Repeated Sprint Ability Test, specifically the 6 × 40 m protocol, to obtain speed endurance indicators (mean sprint time). Data analysis included descriptive statistics, the Shapiro–Wilk normality test, paired t-tests, and independent t-tests. Result. The results showed that RSA training had a significant effect on improving speed endurance in the experimental group. However, the difference test indicated no significant difference between the experimental and control groups in terms of speed endurance (p=.348). In contrast, a significant difference was found in the Fatigue Index (FI) between groups (p=.023), indicating that RSA training was more effective in reducing fatigue and improving the ability to maintain sprint performance under repeated high-intensity conditions. Conclusion. These findings suggest that RSA training is more effective in enhancing fatigue tolerance and maintaining the quality of repeated sprints, as required in rugby sevens. Thus, RSA training is recommended to be systematically integrated into the physical periodization program of back athletes to improve performance readiness in the competition phase.